Efficacy of Exopolysaccharide (EPS) Producing Chromium Resistant Bacteria in the Removal of Chromium from Wastewater - Mazhar, Sumaira; Saleem, Umer (Scientific Inquiry and Review, 2024)
The contamination of heavy metals has caused major health risks, which has particularly led to toxicological manifestations, causing ailments and diseases like irritation of the skin and lungs that can cause nausea and vomiting. Heavy metals; therefore, impart hazardous effects on overall human health due to their potential to accumulate in the living tissues through the food chain mechanism. Conventional remediation strategies have become a challenge to resolve the rising issues of heavy metals. Among different heavy metals, chromium gained much attention due to its prevalence in different oxidation states; however, Cr (III) (less toxic) and Cr (VI) (toxic), are the most prevalent ones. Hexavalent chromium can be converted by some bacteria to the less insoluble and less toxic Cr (III). The current study was conducted to isolate chromium-resistant microbes from the tannery and dye industries, and their potential was evaluated for the reduction of their toxic form. A total number of 13 isolated chromium-resistant bacteria were screened for the production of EPS and out of 13 isolates, 6 were found positive. The effect of temperature (25oC, 30oC, 35oC, 40oC, and 45oC), pH (5, 6, 7, 8, and 9) and time period (24 hours, 48 hours, and 72 hours) on the exopolysaccharides production was examined. It was found that optimum temperature was 35oC, pH was 8, and the time period was 72 hours, respectively, both for the growth and chromium reduction potential. These conditions seemed to be optimum given that the bacteria (alkaliphiles) were isolated from a slightly alkaline environment, which have the ability to grow in a slightly alkaline environment and temperature ranging from 34oC to 36oC. The average chromium reduction potential of EPS-producing bacteria was 91%, and the average growth of these bacteria was 1.0192, respectively. Significant positive correlation was observed between the number of EPS and chromium reduction of EPS-producing chromium-resistant bacterial isolate.